The influence of power distance and collectivism on job satisfaction: The role of organizational trust - Gustiawan, Deni; Jufri, Rusdi Hidayat; Azzahra, Reynia Shifa (Jurnal Bisnis Mahasiswa, 2025)
This study investigates the influence of power distance and collectivism on employee job satisfaction, with organizational trust serving as a mediating variable. Drawing upon Hofstede's cultural dimensions theory and contemporary cross-cultural management research, this research employs Structural Equation Modeling–Partial Least Squares (SEM-PLS) methodology utilizing SmartPLS 4 software. A survey was administered to 350 employees from both public and private sectors across Jakarta, Bogor, Depok, Tangerang, and Bekasi regions in Indonesia. The findings indicate that power distance exerts a significant negative effect on job satisfaction (β = –0.391; p < 0.05), whereas collectivism demonstrates a significant positive effect (β = 0.327; p < 0.05). Furthermore, organizational trust partially mediates the relationship between collectivism and job satisfaction (β = 0.214; p < 0.01), though it does not mediate the relationship between power distance and job satisfaction. These results underscore the critical importance of cultural values in shaping organizational dynamics within Indonesia, a nation characterized by hierarchical structures and collectivist orientations.